Towards a better future for women and work: voices of women and men (Geneva, 2017)
"This study provides a first-ever account of global attitudes and perceptions of women and men regarding women and work based on the 2016 Gallup World Poll. The poll, which was conducted in 142 countries and territories, is representative of 98 per cent of the global population."